2006
DOI: 10.1038/sj.emboj.7601142
|View full text |Cite
|
Sign up to set email alerts
|

Topoisomerase II, not topoisomerase I, is the proficient relaxase of nucleosomal DNA

Abstract: Eukaryotic topoisomerases I and II efficiently remove helical tension in naked DNA molecules. However, this activity has not been examined in nucleosomal DNA, their natural substrate. Here, we obtained yeast minichromosomes holding DNA under ( þ ) helical tension, and incubated them with topoisomerases. We show that DNA supercoiling density can rise above þ 0.04 without displacement of the histones and that the typical nucleosome topology is restored upon DNA relaxation. However, in contrast to what is observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
102
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(112 citation statements)
references
References 63 publications
(83 reference statements)
10
102
0
Order By: Relevance
“…This finding is consistent with the lack of correlation between active transcription of rRNA genes and firing of the adjacent upstream replication origin (52). DNAbinding proteins and chromatin structures can form barriers that impede diffusion of torsional stress and thus increase localized supercoiling (43,64). The promoter-bound UAF complex, which includes histones H3 and H4 and is essential for Pol I transcription and rDNA silencing, is a strong candidate for blocking such dissipation (55).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This finding is consistent with the lack of correlation between active transcription of rRNA genes and firing of the adjacent upstream replication origin (52). DNAbinding proteins and chromatin structures can form barriers that impede diffusion of torsional stress and thus increase localized supercoiling (43,64). The promoter-bound UAF complex, which includes histones H3 and H4 and is essential for Pol I transcription and rDNA silencing, is a strong candidate for blocking such dissipation (55).…”
Section: Discussionsupporting
confidence: 70%
“…However, the absence of Top1 resulted in net negative torsion in many active rRNA genes (as manifested by topo-bubbles), while the inactivation of Top2 resulted in slowed transcription elongation, strongly suggesting net positive supercoiling. Top1 is a torquesensitive topoisomerase and works most efficiently on proteindeficient DNA; Top2 recognizes the double-strand DNA crossovers characteristic of writhed DNA and works better than Top1 on nucleosomal DNA (64). The inability of Top2 to relax the negative topological stress in top1⌬ thus supports the conclusion that such DNA takes the form of melted rather than supercoiled DNA.…”
Section: Discussionsupporting
confidence: 52%
“…Our studies suggest that MGO1 cooperates with chromatin regulators. Therefore, one plausible mechanism is that MGO1 is part of the machinery required to copy chromatin marks during cell division, consistent with the involvement of topoisomerases in chromatin assembly during mitosis in yeast (Garinther and Schultz, 1997;Salceda et al, 2006) and a role of the replication machinery in cellular memory (McNairn and Gilbert, 2003;Vermaak et al, 2003;Barrero et al, 2007;Yin et al, 2009). Supporting this model, mutations in the genes encoding the catalytic subunits of DNA polymerases a and « result in similar phenotypes and genetic interactions as mgo1 (Barrero et al, 2007;Yin et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in yeast suggest that type IB topoisomerase is required for efficient chromatin assembly in mitotically cycling cells (Garinther and Schultz, 1997;Salceda et al, 2006), and a direct involvement in transcription as a positive or negative regulator has been discussed (Merino et al, 1993). It was previously shown that WUS functions as a transcriptional repressor of the cytokinin response regulators (Leibfried et al, 2005) and can interact with TOPLESS (Kieffer et al, 2006), which appears to mediate gene repression via histone H3 deacetylation (Long et al, 2006;Szemenyei et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…There is at present no means to assay higher order coiling within CEN chromatin. However, Top2 has recently been shown to be more proficient than Top1 at relaxing torsional strain on chromatin templates (Salceda et al, 2006), and it seemed possible that biorientation might induce alterations to superhelical winding as CEN fibers were placed under tension. Based on this reasoning, we decided to test whether Top2 might be required to modulate intrachromatid topology at CENs.…”
Section: Cen Superhelicity In Top2 Mutantsmentioning
confidence: 99%